Satisfaction and Interpersonal Closeness as Determinants of Relationship Commitment in Business-to-Business Relationships - Marcel Paulssen (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
The theory of embedded markets states that economic transactions are embedded in social relationships, and economic actors are influenced by both marketing variables and relationship properties. That is, within an exchange relationship actors derive utility from the attributes of a focal product and from interpersonal relationships. We investigate the different roles of satisfaction with a focal product and closeness between boundary personnel in a business-to-business relationship. We demonstrate that these constructs are distinct and differ with respect to antecedents and consequences in a larger nomological network with relationship commitment as the focal dependent variable.
Keywords: 330; Satisfaction; Closeness; Embeddedness